Kajian Literatur: Penggunaan Media Pembelajaran Inovatif Terhadap Peningkatan Pemahaman Konsep Bangun Datar Siswa Sekolah Dasar - Syahnaz Amalia Rizka; Isna Dzulhi Amalina; Muhammad Haikal Maghfir; Fatkhul Arifin (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to examine the effectiveness of innovative learning media on elementary students' understanding of plane geometry concepts. The research method used is a literature review with a descriptive qualitative approach. The findings from various journals reveal that media such as animation videos, educational games, puzzles, and digital applications significantly enhance students’ conceptual understanding. The use of innovative media clarifies abstract concepts, fosters learning interest, and increases students’ active participation. These findings recommend that teachers creatively utilize learning media according to students' characteristics. Innovative media has proven to create more enjoyable, meaningful, and effective learning experiences.